Conclusion: Learnings From Eight Country Studies on Women Entrepreneurs in Asia. Issue 2 (May 2020) - Li, Jessica; Cho, Yonjoo; Chaudhuri, Sanghamitra
The Problem: Women entrepreneurs have played an important role in advancing the economic development of Asian countries. It is in the best interest of Asian countries and international human resource development (HRD) professionals to develop an in-depth understanding of women entrepreneurs in Asia so that they can develop policies, strategies, and resources to support their development. Eight country studies on women entrepreneurs in Asia in this special issue revealed their motivations, challenges, and opportunities in their business start-ups and development. The findings would greatly contribute to an understanding of who women entrepreneurs in Asia are and how they are doing in entrepreneurship. The Solution: The development of women entrepreneurs in Asia requires many scholars and practitioners to study, understand, and theorize before meaningful solutions can be enacted, which will have a lasting impact. This special issue of research on women entrepreneurs in eight Asian countries offers a glimpse of the emerging area of women entrepreneurship. HRD initiatives and expertise are needed to create unchartered possibilities for women entrepreneurs in Asia to succeed and sustain the development of their businesses. The Stakeholders: This special issue is for entrepreneurs and HRD scholars and practitioners who are interested in entrepreneurship development, particularly in the development of women entrepreneurs in Asia.